Hemophagocytic Lymphohistiocytosis (HLH) Following Immune Checkpoint Therapy (ICT) - Saivaroon Gajagowni; Emily Wang; Jianbo Wang; Matthew T. Campbell; Bilal A. Siddiqui (Case Reports in Oncological Medicine)
In the past decade, the use of immune checkpoint therapy (ICT) has increased across many malignancies, including metastatic renal cell carcinoma as an option for frontline and subsequent lines of therapy. Despite the many therapeutic benefits of ICT, its use is complicated by the potential risk of immune-related adverse events (irAEs). One rare but potentially life-threatening irAE is hemophagocytic lymphohistiocytosis (HLH). HLH is a systemic inflammatory disorder resulting in multiorgan failure. The diagnosis of HLH is a challenge due to nonspecific symptoms and overlap with other systemic conditions, which can lead to delays in receiving appropriate treatment and potentially poor patient outcomes. This case illustrates the management of HLH caused by nivolumab plus ipilimumab combination therapy through the use of corticosteroids and tocilizumab in a patient with metastatic clear cell renal cell carcinoma.